Gender dimensions of youth vulnerability toward access to cigarettes in South-East Asia: Evidence from global youth tobacco survey - Satpathy, Nancy; Jena, Pratap Kumar; Epari, Venkatarao (Frontiers in Public Health, 2022)
Background Youths are lured to smoking to make them tobacco customers. Limiting access to tobacco products by youths is a proven strategy to reduce youth tobacco use. This study aimed to examine the burden of cigarette smoking and access to tobacco by youth in South-East Asia (SEA). Methods The burden along with the physical (methods of obtaining cigarettes), financial (cigarette affordability by pocket money), and illegal (sale to minors) access to cigarettes among school-going boys and girls were examined by analyzing the Global Youth Tobacco Survey (GYTS) data (2013–2016) from seven SEA member countries. Descriptive statistics using country-specific GYTS sample weight was used to estimate parameters with 95% confidence intervals. Results The proportion of youths reporting cigarette smoking was highest in East Timor [boys: 55.57 % (51.93–59.21) and girls: 11.35% (9.12–13.59)] and lowest in Sri Lanka [boys: 2.96% (2.91–3.0) and girls: 0%]. Smoking prevalence was higher among boys than girls. Smoking among boys and girls was positively correlated (r = 0.849, p = 0.032). The most common method of obtaining cigarettes was “buying it from a store/kiosk/street hawker” and “other sources.” Except in Indonesia, financial access was limited for most youths. Financial access had a positive but negligible influence on cigarette smoking. Despite legal restrictions on sales to minors, students could obtain cigarettes from vendors. Conclusion Contextual cigarette smoking and access to cigarettes by youths despite the legal ban and unaffordability is a concern. Country-specific socio-cultural-economic and legal dimensions need to be examined to limit cigarette use among youths.